Direct and Indirect Effects of Parental Influence on the Relation Between Violent Offending and Mental Health Problems - Kim, Jihoon (American journal of criminal justice, 2023)
Research has suggested that involvement in offending can contribute to subsequent mental health problems, although the processes through which offending influences adverse mental health remain unclear. Recognizing the need to evaluate intervening factors in this relationship, we focus on the potential mediating role of parenting in the link between offending and mental health problems. Drawing on a sample of serious adolescent offenders from the Pathways to Desistance Study, we test the direct and indirect effects of several dimensions of parenting (hostility, warmth, knowledge, and monitoring) in the relationship between violent offending and mental health problems. Results from multiple mediation models show that violent offending influences mental health problems directly as well as indirectly through parental hostility. Findings suggest that the erosion of social bonds, particularly with parents, may play an important role in understanding the link between offending and mental health problems. In addition, our findings emphasize the potential value of strengthening parent-child relationships in efforts to reduce reoffending.